Respostas
respondido por:
25
fica :
------------------------------------------ somando
- 2,5x = - 10
x = 10 /2,5
x = 4
agora só substituir o x em qualquer uma das equações para encontrar y
y = 6
Anônimo:
valeu
respondido por:
23
2x + 3y = 26 (-2)
3x + 2y = 24 (3)
- 4x - 6y = - 52
9x + 6y = 72
5x = 20
x = 4
2x + 3y = 26 ==> 3y = 26 - 2x
3y = 26 - 2.4 ==> 3y = 26 - 8
3y = 18
y = 6
P( 4, 6 )
.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás